Hubungan antara Gaya Kognitif, Motivasi Berprestasi, dan Lokus Kendali dengan Perolehan Belajar Siswa SMU - Sihkabuden Sihkabuden (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1999)
The study aimed at finding out the relationship between cognitive styles, learning motivation, and locus of control and students’ achievement in Mathematics, Physics, Indonesian, English, Economics, and Geography. The subjects of the study were students of public senior high schools in Malang. The data were in forms of scores of tests on cognitive styles, responses about learning motivation and about locus of control, and scores of summative tests. Correlation and multiple regression were employed to analyze the data. The study found out that there was a positive and significant correlation between cognitive styles and achievement, between learning motivation and achievement (but not in Physics, English, and Geography), and between locus of control and achievement. The cognitive-style variable has an effective contributing power in predicting achievement level.